(untitled) (Modern education and development, 2024)
This article discusses the challenges encountered in translating phraseological units during the translation process between Uzbek and English. It focuses on selecting appropriate equivalents, applying them effectively, and addressing issues arising when there are no direct equivalents between the two languages. The article emphasizes the importance of conveying phraseological units with suitable equivalents in a way that is clear to readers while preserving the original meaning. Additionally, it proposes solutions for ensuring accurate translation while maintaining the essence of the original content.ushbu maqolada ingliz tili va o’zbek tilida tarjima jarayonida duch keladigan frazeologik birliklarni tarjima qilish ularga muqobil variantlar tanlash va ularni tadbiq etish, shu bilan bir qatorda tarjima jarayonida duch keladigan muammolar va ikki til o’rtasida muqobil variantlari bo’lmagan fraziologik birliklarga ekvivalentlar bilan to’ldirish va o’quvchilarga tushinarli shaklda yetkizib berish va shu bilan birgalikda asl mazmunni saqlab qolish muhim ahamiyat kasb etadi. Maqolada asl mazmunni saqlab qolgan holda tarjimani to’g’ri amalga oshirish yechimlari taklif etiladi.